2015
DOI: 10.1007/s12035-015-9315-y
|View full text |Cite
|
Sign up to set email alerts
|

Low Testosterone Level and Risk of Alzheimer’s Disease in the Elderly Men: a Systematic Review and Meta-Analysis

Abstract: Sex steroids can positively affect the brain function, and low levels of sex steroids may be associated with worse cognitive function in the elderly men. However, previous studies reported contrary findings on the relationship between testosterone level and risk of Alzheimer's disease in the elderly men. The objective of this study was to comprehensively assess the relationship between low testosterone level and Alzheimer's disease risk in the elderly men using a meta-analysis. Only prospective cohort studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 28 publications
2
72
0
3
Order By: Relevance
“…The reader is directed to other reviews on sex and gender differences in contribution to disease (Mielke et al, 2014). Indeed, disease progression and manifestation in a number of brain disorders may be influenced by levels of sex steroids (Amiaz and Seidman, 2008; Baum, 2005; Bloch et al, 2003; Lv et al, 2015; McIntyre et al, 2006; Moffat et al, 2004; Rosario et al, 2011; Sankar & Hampson, 2012). For example, lower levels of 17β-estradiol in women are associated with an increased incidence of neurological and neuropsychiatric diseases (Baum, 2005; Rosario et al, 2011; Wieck, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The reader is directed to other reviews on sex and gender differences in contribution to disease (Mielke et al, 2014). Indeed, disease progression and manifestation in a number of brain disorders may be influenced by levels of sex steroids (Amiaz and Seidman, 2008; Baum, 2005; Bloch et al, 2003; Lv et al, 2015; McIntyre et al, 2006; Moffat et al, 2004; Rosario et al, 2011; Sankar & Hampson, 2012). For example, lower levels of 17β-estradiol in women are associated with an increased incidence of neurological and neuropsychiatric diseases (Baum, 2005; Rosario et al, 2011; Wieck, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between low testosterone level and AD is not well understood. A meta-analysis of seven prospective cohort studies with a total of 5251 elderly men and 240 cases of Alzheimer’s disease, supports the view that low testosterone level is significantly associated with increased risk of AD in elderly men, which may suggest that testosterone has important roles in regulating cognitive function in elderly men [115]. Nevertheless, although low testosterone level is a risk factor for AD, a long-term testosterone administration study of 36 months in older men with low or low-to-normal testosterone concentrations treatment did not improve cognitive function [116].…”
Section: Signaling Pathways Participating In Vascular Agingmentioning
confidence: 85%
“…Meta-analysis using random effect model showed that low plasma testosterone level was significantly associated with an increased risk of Alzheimer's disease in elderly men (RR = 1.48, 95% CI 1.12-1.96, P = 0.006) [64]. This decrease is in direct relation with appearance of Aβ plaques in the brain, since androgen and estrogens can regulate the amount of Aβ through the modulation of signal transduction or enzymes related to the clearance of Aβ, like insulin-degrading enzyme, neprilysin, endothelinconverting enzymes 1 and 2, and angiotensin-converting enzyme.…”
Section: Sex Hormones and Alzheimer Diseasementioning
confidence: 99%